Effects of Panax ginseng and Eurycoma longifolia jack extracts on chilled and frozen-thawed crossbred bull semen collected using modified electro-ejaculation method - Ali Baiee, Falah Hasan (2017)
Collection of semen from bulls can be done using different methods. Nowadays, electro-ejaculator technique is known as the most popular method to obtain semen samples from wild and domestic males. Chilled semen does not submit to the freeze-thaw procedure and suffers fewer damages, leading to greater capability and an improved capacity to fertilization. Cryopreservation of sperm plays a considerable role in economization of breeding programs in the cattle herd industry, genetic improvement of domestic animals, preservation of endangered species, and is clinically worthy in the controlling of infertility. Hence, the objectives of the present thesis were: to minimize the discomfort signs during semen collection using electro-ejaculator. Secondly, to evaluate the effect of Panax ginseng aqueous extract on the quality of chilled and frozen-thawed bull semen. Thirdly, to evaluate the effect of Tongkat Ali aqueous extract on the quality of chilled and frozen-thawed bull semen. Finally, to assess the synergistic effect of Tongkat Ali and Panax ginseng extracts on the quality of frozen-thawed bull semen. For all experiments, a total of 84 ejaculates were obtained from six crossbred bulls. The normal automatic electro-ejaculation method of semen collection (Method I) was compared to a modified method involving three stages (stage one, two and three) of gradation electrical stimulation (Method II). Discomfort signs, bulls’ response to electro-ejaculator and fresh semen samples were assessed. Tris-egg yolk extender was used to dilute the semen sample. The extender was prepared into two parts, part one (P1) which did not contain glycerol while part two (P2) contained double amount of glycerol (12.8%). Each semen extender was divided into seven groups containing different concentrations either Panax ginseng aqueous extract, Tongkat Ali aqueous extract or combination between them. Chilled and frozen-thawed semen were carried out. Chilled semen groups were placed in test tube and kept in refrigerator at 5 ºC for 6 days. The frozen semen were packaged in (0.25 mL French straws and cryopreserved in liquid nitrogen (-196 ºC). Sperm motility, morphology, viability, membranes integrity, DNA integrity, and lipid peroxidation were carried out to assess the extracts on chilled and frozen-thawed crossbred bulls. The data were analysed as mean ± standard error of the mean and checked for normal distribution. Descriptive statistical analysis of data, independent samples t-test, one or two-way analysis of variance (ANOVA), Fisher’s exact test, and chi square test were used to analyse the data. The results showed that the discomfortness signs were reduced (P ˂ 0.05), as well as using Method II than Method I. The total time taken for semen collection was similar in both methods. Also, there was no significant difference in fresh semen parameters. Panax ginseng aqueous extract did not improve the functional parameters of chilled and frozen-thawed bull semen. Moreover, sperm DNA integrity of frozen-thawed semen was not improved either. The low dosages (0.25 mg/mL) and (0.5 mg/mL) were not significant compared to control group. However, dosages more than (0.5 mg/mL) showed marked decrease in sperm characteristics (P < 0.01). Tongkat Ali aqueous extract significantly improved the chilled and frozen-thawed semen compared to control. The ideal dose of Tongkat Ali in chilled semen was (1 mg/mL) and (5 mg/mL) in frozen-thawed semen. DNA integrity and lipid peroxidation significantly improved in (5 mg/mL) compared to control group of frozen-thawed semen. In addition, different concentrations of combination between PGe and TAe into Tris-egg yolk extender did not improve the frozen-thawed bull semen quality. In conclusion, the discomfort signs prior and during semen collection were reduced by modification of the automatic mode of the electro-ejaculator device. Panax ginseng aqueous extract did not improve the quality of preserved semen. The quality of chilled and frozen-thawed crossbred bull semen was improved by adding Tongkat Ali aqueous extract to the semen diluent. The combination between Panaxginseng and Tongkat Ali extract also did not improve the quality of frozen-thawed bull semen.